International Students at Chinese Institutions: Trends and Implications - Cai Liu, Nian (International Higher Education, 2020)
China, the world’s largest source of international students, has now become one of the top destination countries for student mobility worldwide and will be a strong competitor in the provision of international higher education in the foreseeable future.